(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
The article focuses on investigating factors influencing the effectiveness of public administration in e-commerce, constructing predictive models, establishing a methodology to evaluate the economic effectiveness of managerial decisions, and suggesting enhancements to management mechanisms in this field within Uzbekistan.